PENGARUH PREFERENSI RISIKO EKSEKUTIF DAN UKURAN PE-RUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Chandra, Jessica Cecilia; Rahardjo, Hartono; Natalia, Irene (Widya Mandala Surabaya Catholic University, 2016)
Tax is one of state revenue sources which is very important for supporting the sustainability of a country's development. A country needs much fund to finance development, thus the government has increased the tax revenue in RAPBN (National budget draft) 2014. This shows that the demand of public tax revenue is increasing. However, the effort to optimize the state fund from tax revenue has many obstacles. One of the obstacles to optimize the tax revenue is tax avoidance. In general, the taxpayers tend to minimalize the amount of tax that should be paid to the state. It causes the tax revenue that should be accepted by the state is not as big as the payments made by the taxpayer. Therefore, this study aimed to examine and analyze the influence of the execu-tive risk preferences and the company size towards tax avoidance in mining companies listed in Indonesia Stock Exchange 2010-2013. This research used quantitative method with hypothesis testing. The dependent variable is tax avoidance, whereas the inde-pendent variables are the executive risk preferences and the company size. The data sources were collected from Indonesia Stock Exchange website and the company’s website as secondary data. Multiple linear regression was used in data analysis technique. The result showed that the executive risk preference and the company size have significant influence on the tax avoidance. Execu-tive risk preferences have significant positive influence on tax avoidance, whereas company size has significant negative influence on tax avoidance.